Effects of corn starch on growth performance of broiler chicks during the early growth period - Rude, Christopher M. (Kansas State University, 2011)
Three experiments were conducted to evaluate the effects of gelatinized starch created during the pelleting process. Effects of gelatinization were first broadly tested to find if either increased or decreased gelatinization levels would increase broiler weight gain and feed efficiency during the starter period, 0 to 21 days of age. Results of the first experiment indicated a decrease (P<0.05) in broiler performance with increased levels of gelatinization, and a significant effect when the inclusion of gelatinized starch in the diet increased from 0 to 35%. A second experiment was conducted using a smaller range, 0 to 21% versus 0 to 35% inclusion of gelatinized starch in the diet and a smaller increment of increase, 3 versus 5%. Results of this experiment confirmed the results of the first experiment, and regression analysis was performed on the data. A linear decrease in body weight gain and quadratic increase in feed:gain (P<0.05) was observed as gelatinized starch was increased from 0 to 21% of the diet. A survey of the literature was conducted showing that most of the simulated levels of gelatinization were larger than those achieved with typical pelleted broiler diets. A third experiment was designed to investigate the levels of gelatinization observed in a pelleted diet and combined with three corn particle sizes, small (466 μm), medium (878 μm), and large (1240 μm), to find if any interactions existed. Chicks fed with the highest gelatinization level of 20%, (7.86% inclusion of pregelatinized starch) had lower body weight gains (P<0.05), and higher feed:gain (P<0.05) compared to chicks fed with 0% gelatinization. Small particle size had the lowest live body weight gain and lowest pen feed intake (P<0.05). There were no interactions found between gelatinization level and particle size (P>0.10). The results demonstrated a negative effect on chick body weight gain and feed efficiency by gelatinization of starch.
Keywords: Broiler; Starter; Starch; Growth performance; Animal Sciences (0475)